Perceptions, intentions, and actual use of a consumer nicotine gum - Cheryl K. Olson; Neil Sherwood; Maia Berkane; Karin Gilligan; Willie J. McKinney (BMC, 2023)
Abstract Background Little is known about perceptions, use intentions, and behaviors of adults regarding nicotine gum that is marketed and regulated as a consumer product rather than as a medicinal nicotine replacement therapy (NRT). Methods Survey data were collected from a Qualtrics online panel (N = 1000) of adults who had never used a consumer nicotine gum, recruited based on smoking behavior, and from current and former purchasers of one commercially available nicotine gum product (LUCY Chew and Park), recruited via emails to a customer database (N = 500). In addition to descriptive cross-sectional analyses, logistic regression was used to estimate the probability of intent to try and of product appeal among these different groups. Results Among online panel respondents, individuals who smoked with and without plans to quit showed high intention to try the product (odds ratios 15.6 [95% CI 9.3, 27.6] and 9.8 [95% CI 5.8, 17.3] respectively, compared to people who formerly smoked) and persons who had never smoked showed low intentions to try. These results stood regardless of flavor. Among current and former purchasers of the study product, 43.4% of persons who had smoked cigarettes regularly indicated they were motivated to try the product "to help me quit smoking." Only 0.6% of young adult consumers of the nicotine gum (aged 21-30) had not tried tobacco products previously. Conclusions Consumer nicotine gum does not appear to attract those who have never used a tobacco product and the results for young adults suggest minimal appeal to youth. The study product was used primarily by individuals who currently smoke and/or use e-cigarettes but who wished to quit or reduce consumption. These results suggest that a consumer nicotine gum may reduce harm by substituting for higher-risk products such as combustible cigarettes.